Transcriptional frameshifts contribute to protein allergenicity - Thouvenot, Benoit; Roitel, Olivier; Tomasina, Julie; Hilselberger, Benoit; Richard, Christelle; Jacquenet, Sandrine; Codreanu-Morel, Françoise; Morisset, Martine; Kanny, Gisèle; Beaudouin, Etienne; Delebarre-Sauvage, Christine; Olivry, Thierry; et al. (The Journal of Clinical Investigation, 2020)
Transcription infidelity (TI) is a mechanism that increases RNA and protein diversity. We found that single-base omissions (i.e., gaps) occurred at significantly higher rates in the RNA of highly allergenic legumes. Transcripts from peanut, soybean, sesame, and mite allergens contained a higher density of gaps than those of nonallergens. Allergen transcripts translate into proteins with a cationic carboxy terminus depleted in hydrophobic residues. In mice, recombinant TI variants of the peanut allergen Ara h 2, but not the canonical allergen itself, induced, without adjuvant, the production of anaphylactogenic specific IgE (sIgE), binding to linear epitopes on both canonical and TI segments of the TI variants. The removal of cationic proteins from bovine lactoserum markedly reduced its capacity to induce sIgE. In peanut-allergic children, the sIgE reactivity was directed toward both canonical and TI segments of Ara h 2 variants. We discovered 2 peanut allergens, which we believe to be previously unreported, because of their RNA-DNA divergence gap patterns and TI peptide amino acid composition. Finally, we showed that the sIgE of children with IgE-negative milk allergy targeted cationic proteins in lactoserum. We propose that it is not the canonical allergens, but their TI variants, that initiate sIgE isotype switching, while both canonical and TI variants elicit clinical allergic reactions.